Developing English for global competence in international business education - Briguglio, Carmela (IDP Education Pty Ltd, 2001)
What are the attributes that the university business graduate of the 21 st centuIy should possess? The answer will depend, largely, on who is asked this question. Although there is some debate as to just which attributes should be developed in such a graduate, there seems to be agreement by all concerned that communication skills are essential, with Australian employers ranking them as even more important than do academics (Sinclair, 1997; Cummings, 1998). In the context of growing trends towards globalisation and the increasing importance of English as a global language, communication skills in English deserve particular attention. This paper examines questions relating to international business education in Australia.'International' should be understood to encompass two aspects: firstly, the fact that large numbers of international students are in the business disciplines in Australia (49.8% in 1999, according to DETYA 2000 statistics); and, secondly, the fact that many Australian universities and Business Schools claim to be preparing students for 'international business' or business in the global arena. For example, the Curtin Business School states as its strategic vision "to provide students with a superb international education through the discovery and application of knowledge" (Curtin Business School, 2001). In this context, this paper seeks to probe what sort of English communication skills might be required for global competence and asks if the necessary skills are being developed in our business courses. The paper then discusses approaches which might best assist students to acquire desirable English communication skills for global competence.